ELECTRONIC METHODOLOGICAL INSTRUCTIONS ON COMPUTER GRAPHICS PREPARATION METHODOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In tis article tey say about preparation and te importance of electron guidelines on te lessons of “computer grapics”.